Identification of GDF-9 and BMP-15 Gene Polymorphisms on Goat Beans - Sri Rahayu (Natural B, Journal of Health and Environmental Sciences, 2011)
The aim of this research was to determine the polymorphisms of BMP-15  and GDF-9 gene of  Kacang goat. DNA was isolated from blood samples of five female goats with salting out method. Quantitative and qualitative  analysis of DNA was measured using spectrophotometer and agarose gel electrophoresis. To get DNA fragment GDF-9 gene was amplified using Forward 5'-AGTTTGTACTGAGCAGGTCT -3 ', Reverse 5'-ACTCCGCTTCGTATGTCAG-3', while to get  DNA fragmen BMP-15 gene was amplified using Forward primer 5’-CAAGGAGGGGACCCCTAAAT-3’, reverse primer 5’- ACCAGAGGCTCAAGAGGAGC-3 for GDF-9. The results of amplification was a specific DNA band with the length of 1400 bp for GDF-9 gene  and 400 bp for BMP-15 gene. Restriction with HaeIII enzyme of GDF-9 PCR product was resulted a haplotype with fragment size 1100 bp, 300 bp, and 100 bp. While, restriction with AluI enzymes of BMP-15 PCR product was resulted a haplotype which consist of two fragments with sizes 180 bp and 120 bp. It was concluded that there are no polymorphism of GDF-9 and BMP-15 gene of Goat Beans.